The Complement of Projection Neurons Activated Determines the Type of Feeding Motor Program in Aplysia - Evans, Colin G.; Barry, Michael A.; Jing, Jian; Perkins, Matthew H.; Weiss, Klaudiusz R.; Cropper, Elizabeth C. (Frontiers in Neural Circuits, 2021)
Multiple projection neurons are often activated to initiate behavior. A question this then raises is, what is the unique functional role of each neuron activated? We address this issue in the feeding system of Aplysia. Previous experiments identified a projection neuron (cerebral buccal interneuron 2 (CBI-2)) that can trigger ingestive motor programs but only after it is repeatedly stimulated, i.e., initial programs are poorly defined. As CBI-2 stimulation continues, programs become progressively more ingestive (repetition priming occurs). This priming results, at least in part, from persistent actions of peptide cotransmitters released from CBI-2. We now show that in some preparations repetition priming does not occur. There is no clear seasonal effect; priming and non-priming preparations are encountered throughout the year. CBI-2 is electrically coupled to a second projection neuron, cerebral buccal interneuron 3 (CBI-3). In preparations in which priming does not occur, we show that ingestive activity is generated when CBI-2 and CBI-3 are coactivated. Programs are immediately ingestive, i.e., priming is not necessary, and a persistent state is not induced. Our data suggest that dynamic changes in the configuration of activity can vary and be determined by the complement of projection neurons that trigger activity.